2002
DOI: 10.3402/fnr.v46i2.1437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on five biochemical microflora-associated characteristics, in vitro and in vivo

Abstract: Background: Several bacterial strains, mainly those belonging to the genera Lactobacillus, Enterococcus, Streptococcus and Bi dobacterium, are currently used as probiotics. Objective: The aim of this study was to investigate the in uence of probiotics on ve biochemical microbial-related functions in vitro and in vivo, in gnotobiotic mice, by applying the G AC:M AC (germ-free animal characteristic:micro ora-associated characteristic) concept. Design: Sixteen probiotics were monoinoculated in vitro and:or monoas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Except for a slight increase in the amount of acetic acid in rats, monoassociation of minipigs and rats with E. coli exerts no influence upon these parameters. This is in agreement with recent studies on association of mice with probiotic strains (Cardona et al., 2002).…”
Section: Discussionsupporting
confidence: 94%
“…Except for a slight increase in the amount of acetic acid in rats, monoassociation of minipigs and rats with E. coli exerts no influence upon these parameters. This is in agreement with recent studies on association of mice with probiotic strains (Cardona et al., 2002).…”
Section: Discussionsupporting
confidence: 94%
“…After 7 days of colonization, the activity increased slowly, especially in caecum, indicating a delayed establishment of this function. Previous in vitro studies have reported a low b-glucuronidase activity in lactobacilli (4,14). The highest activity has always been reported in some E. coli strains; however, the E .…”
Section: Discussionmentioning
confidence: 93%
“…Two reasons may explain that: first, the methods used to test b-glucuronidase activity were slightly different from each other and second, the colonization period for the monoassociation in the present study was much shorter (3 and 7 days) than that of the previous study (60 days). Since the EC X7 strain was highly positive in a qualitative test (14), it may also be a theoretical possibility that the strain behaves differently in vitro and in vivo. Enzyme activity approaching that of the Conv group was found in the mice that were conventionalized for longer, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of MACs has been a major component of studies investigating the contribution of the microbiome in, for example, coeliacs relative to controls, 10,18 probiotic or antibiotic treated infants/children compared with controls 11,19 and even to identify changes in gut microbiota-related functionality due to allergic disease. 12,20 While MACs are useful as a tool for screening large populations, such as in epidemiological studies, they are most useful when supplemented with detailed insights into gut microbial composition.…”
Section: Composition Of the Early Intestinal Microbiotamentioning
confidence: 99%